Tourism Destination Development Planning at Studio Alam TVRI Depok - Mauhammad Rofiq Amirzain; Rizki Nurul Nugraha (West Science Interdisciplinary Studies, 2024)
The research entitled " Tourism Destination Development Planning at Studio Alam TVRI Depok" aims to identify planning strategies applied at Studio Alam TVRI Depok, find out the development of Studio Alam TVRI Depok destinations, and provide insight into the importance of development planning in tourist destinations. This tourist destination is interesting to study considering its considerable tourism potential but has not been done optimally. This type of research is qualitative, with descriptive qualitative analysis methods. Data collection was carried out by field observation, interviews with several resource persons, and literature studies. The results showed that the implementation of planning and development strategies has not been optimal, the success of the development of this destination depends heavily on the integration of systematic and sustainable measures. A focus on technological innovation, sustainable management, and the development of engaging content are key to enhancing the visitor experience and achieving Studio Alam TVRI Depok's strategic goal of becoming a unique and engaging media destination.